Hubungan Keterampilan Berpikir Kritis dan Kesadaran Metakognisi Terhadap Hasil Belajar pada Pembelajaran IPA - Rissa Khairinaa; Daru Wahyuningsih; Annisa Nur Khasanah (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a quantitative research with correlational research design that aims to (1) analyze the relationship between critical thinking skills and knowledge learning outcomes in science learning, (2) analyze the relationship between metacognition awareness and knowledge learning outcomes in science learning, and (3) analyze the relationship between critical thinking skills and metacognition awareness simultaneously on knowledge learning outcomes in science learning. The sampling technique used was cluster random sampling and the sample consisted of 61 students of class VII E and VII H from one of public Junior High School in Surakarta. The research instrument used critical thinking skills test, metacognition awareness questionnaires, and documentation of knowledge learning outcomes. Analysis of the data used Pearson Product Moment Correlation and Multiple Correlations. Based on the data analysis, the results show that (1) there is relationship between critical thinking skills and knowledge learning outcomes in science learning with correlation coefficient of 0.689, (2) there is relationship between metacognition awareness and knowledge learning outcomes in science learning with correlation coefficient of 0.553, and (3) there is relationship between critical thinking skills and metacognition awareness on knowledge learning outcomes in science learning with correlation coefficient of 0.765 and simultaneously contributes 58.5% to knowledge learning outcomes